Dana Pensiun Syariah - Azmi Yusriyah Naurah; Mukhtar Lutfi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Pension funds are an important instrument in financial planning designed to provide financial security for individuals after entering retirement. The main function of pension funds is as a reliable source of income to meet living needs in old age, as well as contributing to the quality of life and individual welfare. Research shows that pension funds can reduce financial risks, such as job loss and unexpected conditions that can interfere with work ability]. In addition, employees who prepare well for their retirement funds tend to experience lower levels of anxiety as they approach retirement, which shows that good planning can improve the quality of life]. The existence of pension funds also contributes to social and economic welfare, with adequate pension guarantees that can increase household consumption and support economic growth.. In the context of sharia pension funds, fund management is carried out based on sharia principles which prohibit the practice of usury and gharar, and implement transparency and social responsibility. The application of sharia contracts in the management of sharia pension funds, such as murabahah contracts, allows management in accordance with Islamic ethical principles. Sharia financial literacy is also a key factor in increasing public participation in sharia pension fund programs. Thus, effective retirement fund planning not only meets basic needs in old age, but also contributes to social and economic well-being, and improves the quality of life of individuals.